Colleague relationships as a stress factor for special needs school teachers: A comparison with other public schools - Masateru Matsushita; Schuhei Yamamura (PCN Reports)
Abstract Aim Although teachers in special needs schools do not always work long hours, their sick leave rate is higher than that of teachers in other types of schools. We aimed to compare the causes of stress between teachers in public special needs schools and different public schools and explore the stress factors among teachers in special needs schools. Methods An Internet‐based cross‐sectional survey was conducted between June and December 2021. We analyzed the data of 203,433 teachers with no missing values, including 15,159 teachers from special needs schools. Demographic variables, stress factors, psychological and physical stress responses, job satisfaction, and working hours were analyzed. Results Among high‐stress teachers, 30.4% of the special needs school teachers had difficulties with their relationships with their colleagues; these difficulties were statistically significantly more frequent than for teachers in other school types (15.1% in elementary, 17.6% in junior high, and 19.1% in high schools). Multiple logistic regression analysis revealed that high‐stress teachers in special needs schools were 1.82 times more likely than teachers in other types of schools to be stressed by their relationships with colleagues after controlling for age, sex, teaching experience, size of school, working hours per day, and job satisfaction (95% confidential interval = 1.65–2.01, Wald = 137.3, p ≤ 0.001). Conclusion The findings suggest that not only a reduction in working hours but also the cultivation of human relationships and a cooperative working environment in the workplace may be effective in eliminating stress among teachers in special needs schools.